2013
DOI: 10.1016/j.cell.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome-free Region Dominates Histone Acetylation in Targeting SWR1 to Promoters for H2A.Z Replacement

Abstract: Summary The histone variant H2A.Z is a genome-wide signature of nucleosomes proximal to eukaryotic regulatory DNA. While the multi-subunit chromatin remodeler SWR1 is known to catalyze ATP-dependent deposition of H2A.Z, the mechanism of SWR1 recruitment to S. cerevisiae promoters has been unclear. A sensitive assay for competitive binding of di-nucleosome substrates revealed that SWR1 preferentially binds long nucleosome-free DNA and the adjoining nucleosome core particle, allowing discrimination of gene promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
182
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(211 citation statements)
references
References 77 publications
(111 reference statements)
26
182
2
1
Order By: Relevance
“…The ATP-dependent SWR1 chromatin remodeling complex (SWR1-C) catalyzes the replacement of H2A-H2B dimers with H2A.Z-H2B dimers in nucleosome structures, thus producing variant nucleosomes with dynamic properties (Mizuguchi et al, 2004;Luk et al, 2010). The H2A.Z-containing nucleosomes preferentially localize around transcription start sites and in the vicinity of the genes where SWR1-C is recruited, through the direct DNA binding of the SWR1 and SWC2, components of the complex (Raisner et al, 2005;Deal et al, 2007;Zilberman et al, 2008;Jin et al, 2009;Ranjan et al, 2013;Yen et al, 2013).…”
mentioning
confidence: 99%
“…The ATP-dependent SWR1 chromatin remodeling complex (SWR1-C) catalyzes the replacement of H2A-H2B dimers with H2A.Z-H2B dimers in nucleosome structures, thus producing variant nucleosomes with dynamic properties (Mizuguchi et al, 2004;Luk et al, 2010). The H2A.Z-containing nucleosomes preferentially localize around transcription start sites and in the vicinity of the genes where SWR1-C is recruited, through the direct DNA binding of the SWR1 and SWC2, components of the complex (Raisner et al, 2005;Deal et al, 2007;Zilberman et al, 2008;Jin et al, 2009;Ranjan et al, 2013;Yen et al, 2013).…”
mentioning
confidence: 99%
“…The Swr1 complex binds to acetylated histones in general to preferentially deposit H2A.Z at acetylated regions of the genome [55]. However, recent studies by Ranjan et al showed that recognition of a nucleosome-free region by the Swr1 complex was more efficient for its targeting to DNA than recognition of acetylated chromatin [56]. The link between histone acetylation and SWR1 targeting may also depend on the site of acetylation since hyperacetylation of H3K56 was found to antagonize binding of Swr1 complex and prevent H2A.Z deposition in yeast [57].…”
Section: H2az Localization and Depositionmentioning
confidence: 93%
“…Despite these strong correlations, the causal role of H2A.Z for gene expression is more nebulous as genome-wide expression studies found that loss of H2A.Z affects only a minority of genes in yeast (Meneghini et al 2003). In recent years, many studies have suggested that rather than affecting steady-state gene expression, H2A.Z may facilitate the induction of genes in response to changing environments (Adam et al 2001;Larochelle and Gaudreau 2003;Lemieux et al 2008;Halley et al 2010).H2A.Z is deposited into chromatin by SWR1-C, an ATPasedependent chromatin remodeling complex that recognizes the NFR and exchanges H2A-H2B dimers with H2A.Z-H2B dimers at the two flanking nucleosomes (Krogan et al 2003;Kobor et al 2004;Mizuguchi et al 2004;Ranjan et al 2013). Illustrative of the cross-talk between chromatin remodelers, SWR1-C and the NuA4 histone acetyltransferase (HAT) have interconnected activities converging on H2A.Z chromatin neighborhoods.…”
mentioning
confidence: 99%
“…Illustrative of the cross-talk between chromatin remodelers, SWR1-C and the NuA4 histone acetyltransferase (HAT) have interconnected activities converging on H2A.Z chromatin neighborhoods. Acetylation of H4 lysine residues by NuA4 promotes the recruitment of SWR1-C for H2A.Z deposition, and subsequent acetylation of newly incorporated H2A.Z by NuA4 is required for gene activation and heterochromatin formation (Babiarz et al 2006;Durant and Pugh 2007;Altaf et al 2010;Ranjan et al 2013). The interplay between SWR1-C and NuA4 likely involves a module of four subunits that is shared between the two complexes (Lu et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation